Evidence of Microglial Immune Response Following Coronavirus PHEV Infection of CNS - Zhang, Jing; Li, Zi; Lu, Huijun; Shi, Junchao; Gao, Rui; Ma, Ying; Lan, Yungang; Guan, Jiyu; Zhao, Kui; Gao, Feng; He, Wenqi (Frontiers in Immunology, 2022)
Porcine hemagglutinating encephalomyelitis virus (PHEV) is a highly neurotropic coronavirus that invades the host central nervous system (CNS) and causes neurological dysfunction. Microglia are key immune cells in the CNS, however, whether and how they response to PHEV infection remains unclear. Herein, microglial activation and proliferation were detected in the CNS of PHEV-infected mice, as along with the proinflammatory response. Moreover, the production of proinflammatory cytokines induced by moderately activated microglia limited viral replication in the early stage of infection. Microglial depletion assays showed that during late infection, excess activation of microglia aggravated neurological symptoms, BBB destruction, and peripheral monocyte/macrophage infiltration into the CNS. Using an in vitro brain slice model, PHEV was identified to specifically and moderately induce microglial activation in the absence of peripheral immune cells infiltration. Consistently, macrophage clearance from circulating blood indicated that peripheral monocytes/macrophages crossing the BBB of mice were responsible for excess activation of microglia and CNS damage in late PHEV infection. Overall, our findings provide evidence supporting a dual role for microglia in the host CNS in response to coronavirus PHEV invasion.